Deglacial paleoseismicity in Sweden:the 9663 BP Iggesund event - Mörner, Nils-Axel; Tröften, Per Einar; Sjöberg, Rabbe; Grant, Douglas; Dawson, Sue; Bronge, Christian; Kvamsdal, Ole; Sideén, Alf (Quaternary Science Reviews, 2000)
The Iggeesund event is an example of the high seismicity which occurred in Fennoscandia during deglaciation as a function of the high rate of glacial isostatic uplift. This event is dated to varve 9663 BP. The Iggesund-Hudiksvall area is represented by intensive postglacial fracturing of the bedrock recorded over an area of at least, 50 x 50 km. The most remarkable locality is the Boda cave system; a hill fractured into a field of large detached blocks with a cave system of more than 2 km length. In the varve-year 9663 BP, an extensive turbidite was spread over an area of 210 x 80 km. Liquefaction structures are recorded over an area of 80 x 30 km and can be assigned to the same varve year. Structures and deposits of a tsunami are recorded over 80 x 50 km.